2013
DOI: 10.1080/01690965.2012.672754
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of complex argument structure representations: Processing “alternating transitivity” verbs

Abstract: This study examines the neural correlates of processing verbal entries with multiple argument structures using fMRI. We compared brain activation in response to ‘alternating transitivity’ verbs, corresponding to two different verbal alternates – one transitive and one intransitive - and simple verbs, with only one, intransitive, thematic grid. Fourteen young healthy participants performed a lexical decision task with the two verb types. Results showed significantly greater activation in the angular and suprama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
6
23
2
Order By: Relevance
“…* burst something at the seam ) (see Horvath & Siloni, 2009, for discussion of similar facts in Hebrew). Moreover, in Meltzer-Asscher et al (2012) we found activation in bilateral AG and MFG in response to alternating unaccusative compared to unergative verbs. In that study, the posterior activation was argued to reflect processing associated with the greater number of thematic roles associated with the transitive reading of the alternating verbs (as in Thompson 2007, 2010 and the current study), and the frontal activation was interpreted as emerging from the processing of lexical ambiguity, namely the existence of multiple thematic options for the alternating verbs.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…* burst something at the seam ) (see Horvath & Siloni, 2009, for discussion of similar facts in Hebrew). Moreover, in Meltzer-Asscher et al (2012) we found activation in bilateral AG and MFG in response to alternating unaccusative compared to unergative verbs. In that study, the posterior activation was argued to reflect processing associated with the greater number of thematic roles associated with the transitive reading of the alternating verbs (as in Thompson 2007, 2010 and the current study), and the frontal activation was interpreted as emerging from the processing of lexical ambiguity, namely the existence of multiple thematic options for the alternating verbs.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, lexicalist approaches (e.g. Horvath & Siloni, 2010; Meltzer-Asscher, 2012; Reinhart, 2002) argue that detailed thematic grids must be specified in the lexicon. Other approaches (e.g.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent years, however, have brought us numerous aphasia and neuroimaging studies focusing on verb meaning and structure (e.g., Bastiaanse and van Zonnevelt 2005;Faroqi-Shah and Thompson 2010;Kemmerer 2006;Kemmerer and Eggleston 2010;Meltzer-Asscher et al 2013;; Thompson et al 2007Thompson et al , 2010.…”
mentioning
confidence: 99%